Desenvolvimento de um sistema ótico para aplicação na monitoração da marcha humana - Kamizi, Marcos Aleksandro (2020)
This work shows the multiplexing ability and applicability of macrobend optical fiber sensors produced by the encapsulation of an optical fiber ring in silicone elastomer. Sensing is based on the detection of intensity changes in the optical signal transmitted by one or more sensors. These intensity changes are related to macrocurvature modifications occurring when the sensors are affected by external parameters. Two sensing systems were developed and tested for monitoring the human gait. In these systems, the optical signal transmitted by the macrocurvature sensors in the visible spectral range is detect by the camera of a smartphone. The first system contains two heel cups, each one instrumented with only one macrocurvature sensor. The second system uses a pair of insoles, each one containing three sensors. Details of the working principle, optical source setup, sensors fabrication, interrogation system and methodology for signal processing and data analysis are discussed. Shoes containing the heel cups and the insoles were used in the characterization and test stages. The results of the experimental tests have shown the sensing systems ability of identifying spatial and temporal parameters of the gait as well as ground reaction forces. The system with a pair of insoles tested in a simulated gait, provided the stride length of 1.27 m, stride time of 2.49 s, step time of 1.25 s, walking speed of 0.51 m/s, cadence of 48 steps/min and double and single support times of 0.97 s and 0.73 s, respectively. Additionally, 6 multiplexed in-series macrocurvature sensors were employed in a load detection system. A linear regression model was used to estimate different load configurations applied on the sensors from the system transmission spectra. The training and test steps were performed with a set of 411 load configurations. A mean absolute error of 0.12 kg corresponding of 7.8% of the maximum load per sensor was obtained in the test step. Finally, the systems are easy to produce and manipulate and because it is portable, it differs from other techniques, providing flexibility of use in gait monitoring.